Effect of Scalp-acupuncture Treatment on Language Reorganization in Poststroke Aphasia：A Functional Near-Infrared Spectroscopy - LIN Bingbing; NI Jinglei; XIONG Xiao; HUANG Yunshi; HUANG Jia (康复学报)
Objective Based on functional near infrared spectroscopy （fNIRS），to explore the scalp targeting language function and its neurological mechanism of action in patients with post-stroke aphasia （PSA）. Methods A total of 64 PSA patients hospitalized in the Rehabilitation Hospital Affiliated to Fujian University of Traditional Chinese Medicine from July 2022 to September 2023 were selected，and a table of random numbers was generated using SAS 9. 1 statistical software，and each group was divided into a control group and an observation group according to a 1：1 ratio，with 32 cases in each group. The control group received conventional speech rehabilitation therapy （speech training，language imitation，figure-word matching，numerical reading/writing/calculating and social communication skills training，etc. ），medication and health education; the observation group received scalp acupuncture on the basis of the control group，selecting the language function area （2/5 below the parietal anterior temporal diagonal line and the anterior temporal line），and then stabbing it either flatly or obliquely，and then retained for 30 minutes post-needling sensation （deqi），and the speech and language treatment was carried out by the speech rehabilitation therapist in the process. Both groups were treated for 30 min/session，once/day，5 times/week for 4 weeks. Before and after the treatment，the patients were evaluated by the Beijing Medical University Aphasia Battery of Chinese （ABC）; the patients were evaluated by the Chinese Functional Communication Profile （CFCP）; the subjects were tested for changes in cortical hemoglobin oxyhemoglobin （HbO2） and hemoglobin deoxyhemoglobin （HbR） by using the fNIRS; and the patients were evaluated by using the verbal fluency task by using the E-prime 3. 0 software. The correlation between the activation of brain regions during the verbal fluency task and the verbal fluency scores of the observation group was analyzed. Results （1）ABC，CFCP and verbal fluency scores：Compared with the pre-treatment period，the ABC，CFCP and verbal fluency scores of the two groups increased significantly after treatment，and the difference was statistically significant （P<0. 05）. Compared with the control group，the differences in ABC and CFCP scores of the observation group were not statistically significant after treatment （P>0. 05），and the verbal fluency scores were significantly higher after treatment （P<0. 05），and the differences in the scores before and after the treatment of ABC，CFCP and verbal fluency were significantly higher，and the differences were all statistically significant （P<0. 05）. （2）Brain area activation β-value during the verbal fluency task：compared with the control group，the observation group had significantly higher activation β-value in the left posterior part of the middle temporal gyrus （P=0. 037），and significantly lower activation β- value in the right inferior frontal gyrus deltoid part of the brain area （P=0. 022） and in the right posterior part of the middle temporal gyrus （P=0. 05）. （3） Correlation between the activation β-value of brain regions during the verbal fluency task and the verbal fluency score differentials：the verbal fluency score differentials of the observation group were negatively correlated with the activation β-value of the posterior portion of the right middle temporal gyrus （r=-0. 408，P=0. 020），and the activation β-value of the right pars triangularis gyri frontalis inferioris （r=-0. 423，P=0. 016）. Conclusion Scalp acupuncture treatment combined with speech and language therapy can promote the recovery of language function in PSA patients，in which the improvement of verbal fluency may be related to the down-regulation of activation of the posterior part of the right middle temporal gyrus and the right pars triangularis gyri frontalis inferioris.